THE PLACE OF PERSPECTIVE IN COLOR PICTURES - Abdusattorova Dildora Rafikjon Kizi (Galaxy International Interdisciplinary Research Journal, 2022)
Perspektiva (Latin perspicio - I see clearly) is a system of depicting the spatial position of an existing being on a flat surface (paper, board, wall, etc.) as perceived by man, and their distance from the point of observation. It is the basis of realistic fine arts. Linear Perspective is the ability to create an accurate representation of the structure of different positions and appearances of real objects in space, as well as the characteristics of their size. bersa, havo (color) Perspective. It serves to create an accurate and reliable image of the change in color and boundaries of objects as they move away from the point of observation. Observation Perspective is used in art.